2017
DOI: 10.1016/j.arthro.2017.08.269
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: The Wake of the Dragon: Will the Orthopaedic Community Adopt the Shoulder Arthroscopic Latarjet Procedure as We Adopted the Arthroscopic Rotator Cuff Repair?

Abstract: The Latarjet procedure is a complex and difficult operation when performed both with an open approach and arthroscopically. The difficulties come from the fact that it is a combined intra- and extra-articular procedure, and that working close to the brachial plexus may be frightening for surgeons. Because of the high complication and reoperation rates reported in the literature, this procedure is, at the moment, rejected by a large part of the orthopaedic community, specifically in North America. The Chinese e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The paper has been cited almost 500 times in 10 years [1] and is often used to guide the surgical choice in published work [7, 8, 19] and in meetings, especially in France and Europe, but also around the world [25]. Later on, Boileau and Saliken [4] and others [7, 19] have suggested that the threshold to avoid an arthroscopic Bankart repair should be lowered to 4. Our results clearly dispute this suggestion as we could not find an increased recurrence risk for patients scoring above 3 when compared to those with lower values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper has been cited almost 500 times in 10 years [1] and is often used to guide the surgical choice in published work [7, 8, 19] and in meetings, especially in France and Europe, but also around the world [25]. Later on, Boileau and Saliken [4] and others [7, 19] have suggested that the threshold to avoid an arthroscopic Bankart repair should be lowered to 4. Our results clearly dispute this suggestion as we could not find an increased recurrence risk for patients scoring above 3 when compared to those with lower values.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were: (1) recurrent anterior instability [dislocation or subluxation] with or without hyperlaxity and (2) an arthroscopic Bankart repair The exclusion criteria were: (1) concomitant rotator cuf lesion, (2) an acute irst-time dislocation, (3) surgery for recurrent instability after a previous anterior stabilization, (4) surgery for a painful, unstable shoulder without true dislocation or subluxation; or (5) multidirectional instability. Those inclusion and exclusion criteria followed precisely those used by Balg and Boileau in their initial ISIS study [3].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous surveys in other geographic regions have been completed to date outlining the areas of consensus and contention in clinical practice, as well as an evolution in practice patterns over time. [18][19][20][21][22][23][24][25] This includes a shift toward arthroscopic over open procedures, [26][27][28] a reduction in nonoperative management of those with an initial shoulder dislocation, and a subsequent acceptance that surgical stabilization may be an appropriate first course of action. 29,30 The arthroscopic Bankart repair is often the treatment of choice in the absence of bony pathology.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Frozen shoulder is primary adhesive capsulitis that can be attributed to various factors such as shoulder joint infection, long-term immobilization of the shoulder joint, and upper limb trauma. 2 Most frozen shoulders may occur concurrently with rotator cuff injuries, with the incidence accounting for 35% of rotator cuff injuries. 3 Once combined, the limitation of shoulder joint movement and pain will be aggravated, and early treatment is needed to alleviate the symptoms.…”
Section: Introductionmentioning
confidence: 99%